The use of translation for English teaching in Indonesia: an attempt to reclaim its legitimacy - Futuh Handoyo (Jurnal Linguistik Terapan, 2013)
Translation and English teaching have had a long relation since the use of grammar translation methods. With the advance of communicative approach, translation seems to occupy a neglected room in language teaching. Drawing on several theories, this article builds arguments that translation should have a good place and an important role to play in language teaching. Further, this article also present teaching scenario using translation in English classes.